Disposition to pediatric intensive care unit post supraglottoplasty repair: a systematic review - Esther ShinHyun Kang; Sena Turkdogan; Jeffrey C. Yeung (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Patients undergoing supraglottoplasty are often routinely admitted post-operatively to the pediatric intensive care unit (PICU) due to rare but potentially fatal complications such as airway compromise. A systematic review was performed to determine the rate of post-operative PICU-level respiratory support required by pediatric patients following supraglottoplasty, to identify risk factors for patients who may benefit from post-operative PICU admission and limit unnecessary use of intensivist resources. Review methods Key search terms ‘supraglottoplasty’ OR ‘supraglottoplasties’ were queried on three databases: CINHAL, Medline and Embase. Inclusion criteria were pediatric patients under 18 years of age who underwent a supraglottoplasty procedure with either an admission to PICU or requirement for PICU-level respiratory support. Risk of bias was assessed by two independent reviewers using QUADAS-2. Findings were critically appraised by three independent reviewers and pooled proportions of criteria meeting PICU admission were calculated for meta-analysis. Results Nine studies met inclusion criteria, totaling 922 patients. Age at time of surgery ranged from 19 days to 15.7 years with mean age of 5.65 months. A weighted pooled estimate suggested that 19% (95% CI 14–24%) of patients who underwent supraglottoplasty required PICU-admission. The included studies revealed several patient and surgical factors have been linked to postoperative respiratory issues requiring PICU admission, including: neurological disease, perioperative oxygen saturation < 95%, prolonged surgical time and age < 2 months. Conclusions This study found that the majority of supraglottoplasty patients do not require significant postoperative respiratory support and suggests that routine PICU admission of these patients may be avoided by careful patient selection. Given the wide heterogeneity of outcome measures, further studies are needed to determine the ideal PICU admission criteria following supraglottoplasty. Graphical Abstract